Integrasi Konseptual Zakat dan Pajak dalam Kerangka Negara Kesejahteraan: Telaah Literatur Kebijakan Fiskal Indonesia - Nawawi, Tolhah Toha; Sayuti, Sayuti (Universitas Muara Bungo, 2025)
Abstract: This study aims to analyze the conceptual integration between zakat and taxes within the framework of the Indonesian welfare state as an effort to realize a fair, inclusive, and sustainable fiscal system. The research method used is qualitative with a descriptive approach through library research sourced from scientific journals, books, and official documents related to Islamic fiscal policy. Data collection techniques were carried out through literature searches and document analysis, while data analysis included the stages of theme identification, data reduction, concept categorization, and inductive conclusion drawing. The results show that the integration of zakat and taxes has a complementary function in the public financial system: zakat plays a direct role in wealth redistribution and poverty alleviation, while taxes support development financing and economic growth. The synergy between the two is considered capable of increasing social justice, strengthening the moral legitimacy of fiscal policy, and encouraging the creation of a welfare state based on maq??id al-syar?‘ah. However, normative, institutional, and fiscal literacy challenges remain major obstacles that need to be overcome through legal reform, digital system integration, and improved coordination between institutions such as BAZNAS, LAZ, and the Directorate General of Taxes. This research contributes to the development of Islamic economic theory and fiscal policy by offering an applicable model of zakat-tax synergy for strengthening distributive justice in Indonesia.Keywords: Zakat, Tax, Fiscal Policy, Welfare State, Islamic Economics